Redescription of Periclimenes brockii (De Man, 1888) (Decapoda: Caridea: Pontoniinae) and other De Mans type specimens deposited in the collection of the Senckenberg Natural History Museum (SMF), Frankfurt-at-Maine, Germany - Marin, Ivan; Türkay, Michael (Zootaxa, 2009)
The type specimens of 3 species described by Dr. Johannes Govertus De Man, Cuapetes amymone (De Man, 1902), Periclimenella spinifera (De Man, 1902), Periclimenes brockii (De Man, 1888), were re-examined in the collection of the Senckenberg Natural History Museum (SMF), Frankfurt-at-Maine, Germany. Periclimenes brockii De Man, 1888 is found to be a senior synonym of Allopontonia iaini Bruce, 1972 and Periclimenes priodactylus Bruce, 1992.